Psychedelic researchers’ own experiences of psychedelic substances, their link to opinions of psychedelics, and reflections on positionality - Jylkkä, Jussi; Mustamo, Aila (Springer Nature, 2026)
Rationale: Anecdotal evidence suggests that psychedelic researchers often have personal experiences with psychedelic substances. While such experiences may benefit research, concerns have been raised about potential biases and "excessive enthusiasm." However, the prevalence of personal experiences, their perceived relevance, and their association with opinions about psychedelics remain underexplored.
Objectives: This study aimed to investigate how common personal psychedelic experiences are among psychedelic researchers, their perceived relevance to research, and whether personal use is associated with opinions about psychedelics.
Methods: Participants (N = 111) conducting psychedelic research in academic settings were recruited. Data were collected on personal experiences, their perceived relevance, and opinions about psychedelics. Regression analyses examined associations between personal use and opinions.
Results: Most respondents (85%) reported personal experiences with classic psychedelics. On average, they saw personal experience as beneficial for research, but also as potential source of bias. They acknowledged the importance of self-reflection and the need to disclose personal experiences, but found disclosure challenging in practice. Personal use predicted more positive opinions about psychedelics' potential to improve well-being, transform society, address the ecological crisis, and answer spiritual questions (regression βs = 0.3 - 0.5, ps < 0.01).
Conclusions: The findings highlight the prevalence of personal psychedelic experiences among this sample of researchers and their influence on research interests and opinions. The results underscore the need for open discussion and reflection. Future studies should explore whether the observed associations reflect causal relationships or potential biases.